2011
DOI: 10.1007/s12011-011-9009-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Heavy Metals on Developmental Stages of Ovule, Pollen, and Root Proteins in Reseda lutea L. (Resedaceae)

Abstract: Heavy metals are some of the most important environmental pollutants. Excessive amounts of heavy metals adversely affect plant growth and development. Also, the presence of elevated levels of heavy metal ions triggers a wide range of cellular responses including changes in gene expression and synthesis of metal-detoxifying peptides. The overall objective of this research was to elucidate some microscopic effects of heavy metals on the formation, development, and structure of pollen, ovule, and embryo and also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…All heavy metals at high concentrations have strong toxic effects and are regarded as environmental pollutants [6,7,8].…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…All heavy metals at high concentrations have strong toxic effects and are regarded as environmental pollutants [6,7,8].…”
Section: Disscusionmentioning
confidence: 99%
“…Sawidis [5] showed that heavy metals have toxic effect on the pollen growth and pollen tube growth and cause to be a range of strong morphological abnormalities, characterized by uneven or aberrant growth, including apical branching or swelling at the tip of the pollen tube. Several researchers also showed toxic effects of heavy metals on different organisms [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is unknown whether most serpentine plants accumulate Ni into pollen grains, despite evidence that plants growing in soils contaminated by metals via human activities can accumulate them into pollen (Moroń et al 2012). Metals in pollen could reduce germination (citations above; Mohsenzadeh et al 2011; Yousefi et al 2011 a ) or pollinator attraction (Meindl and Ashman 2014), and Ni accumulation in nectar can affect pollinator foraging (Meindl and Ashman 2013, 2014). Thus, a first and necessary step towards understanding the reproductive consequences of growth on serpentine soil is documenting metal concentrations of reproductive organs and floral rewards of non-hyperaccumulating serpentine plants, as well as determining whether or not non-hyperaccumulating endemic species are better able to avoid potentially deleterious effects of metals by excluding them from reproductive organs than non-endemics.…”
Section: Introductionmentioning
confidence: 99%
“…We were also intrigued how metals are distributed between plant vegetative and generative organs. Mohsenzadeh et al (2011) showed that the excessive amounts of heavy metals negatively affect plant growth and development, including the development of the ovules and embryos. Musielińska et al (2016) showed the lower concentration of zinc in flowers than in leaves of the closely related E. ramosus (Walters) Britton, Sterns & Poggenb., as well as in many other species from the family of Asteraceae.…”
mentioning
confidence: 99%